Adoptive cell transfer of piezo-activated macrophage rescues immunosuppressed rodents from life-threating bacterial infections - Xiaoyi Liu; Wenxiu Xu; Junkun Feng; Ying Wang; Kai Li; Yi Chen; Wenjun Wang; Weiwei Zhao; Shaohua Ge; Jianhua Li (Nature Communications)
Abstract Bacterial infections pose a significant threat to human health. Catalytic antibacterial nanoparticles that generate reactive oxygen species (ROS) are emerging, as a promising therapeutic approach in treating bacterial infection by boosting the innate immune defenses. However, the interaction between innate immune cells and these catalytic nanoparticles remains poorly understood. Here, by using rodent models of bacterial infection, we test the antimicrobial properties of ultrasound-responsive piezo-catalytic nanoparticles (piezoNP). We show that piezoNPs strongly interact with macrophages within subcutaneous abscesses caused by Staphylococcus aureus (S. aureus) infections, and demonstrate that this interaction enhances the macrophage-mediated antibacterial phagocytosis and killing activity through intracellular piezocatalysis. Moreover, we test the use of these piezo-activated macrophages (piezoMϕ) as adoptive cell therapy (ACT) for treating various immunosuppressive bacterial infections, including sepsis, pneumonia and peritonitis. Our study thus highlights the potential application of catalytic nanoparticles as a promising alternative to conventional infection treatment to effectively modulate the innate immune responses and to engineer macrophages for immunotherapy purposes.